The Function of PsbS Protein in Plant Photosynthesis Regulation - Hương, Thu Khương Thị; Robaglia, Christophe; Caffarri, Stefano (VNU Journal of Science: Natural Sciences and Technology; Vol 30 No 2, 2014)
Abstract: Photosynthesis transforms sun light energy into chemical energy of organic compounds, which sustain almost all life on the planet. In high light conditions, the energy absorbed that excess their photosynthesis capacity can be formed ROS (Reactive Oxygen Species) that are very dangerous for plant. To prevent ROS and plant photoprotection, the plant develop a mechanism which harmlessly dissipate excess light energy absorbed as heat called NPQ (Non Photochemical Quenching). In this paper, we review the researches of PsbS protein of photosystem II  which is known have a key role in the NPQ  activation. The NPQ capacity is correlate to PsbS level in plant leaf. The protein PsbS is as sensor of lumenal pH for NPQ activation. It is also proposed reorganisation control of grana membrane in high light condition. This protein maybe is not bound pigments, but it is related to zeaxanthin for complete NPQ activation. So PsbS has the important role for resistance of plant to high light. The investigation of PsbS protein could open the photosynthesis light harvesting regulation perspective for improve plant productivity. Keywords : Light, NPQ, photosynthesis, PsbS protein, ROS.